PENGARUH PROSES PENGERINGAN TERHADAP NILAI PLASTISITAS RETENSI KARET REMAH - Akli, Khairul; Febrian, Aby; Samah, Selfa Dewati; Maryam, Maryam (Politeknik ATI Padang, 2023)
The crumb rubber SIR 20 originating from the processing of natural rubber (Hevea brasiliensis) plays a crucial role as a primary export commodity in the Indonesian economy. Due to its diverse applications in consumer products and medical devices, natural rubber possesses unique properties such as resilience, elasticity, and wear resistance. The drying process of natural rubber at high temperatures significantly affects its plasticity and strength. This research explores the influence of temperature (130-155°C) and drying time (77-110 minutes) on the plasticity of crumb rubber SIR 20. The results indicate that the PRI (Plasticity Retention Index) values still meet quality standards within certain ranges. The optimal PRI value of 75-76% is obtained at a temperature of 130-135°C for 77 minutes. Increasing the operating temperature and drying time leads to a significant decrease in PRI values due to thermal oxidation occurring in the molecular structure of rubber, thereby affecting the quality of crumb rubber. The findings from this study on the impact of temperature and drying time can provide technical information for the rubber industry to maintain product quality while minimizing environmental impact.